Pathogenic Differences of Type 1 Restriction-Modification Allele Variants in Experimental Listeria monocytogenes Meningitis - Zbinden, Florian R.; De Ste Croix, Megan; Grandgirard, Denis; Haigh, Richard D.; Vacca, Irene; Zamudio, Roxana; Goodall, Emily C. A.; Stephan, Roger; Oggioni, Marco R.; Leib, Stephen L. (Frontiers in Cellular and Infection Microbiology, 2020)
Background L. monocytogenes meningoencephalitis has a mortality rate of up to 50% and neurofunctional sequelae are common. Type I restriction-modification systems (RMS) are capable of adding methyl groups to the host genome. Some contain multiple sequence recognition (hsdS) genes that recombine, resulting in distinct DNA methylation patterns and patterns of gene expression. These phenotypic switches have been linked to virulence and have recently been discovered in multiple clonal complexes of L. monocytogenes. Methods L. monocytogenes strains containing RMS systems were identified, and purified clones enriched for single hsdS alleles were isolated. In vivo, 11-day old Wistar rats were infected with an inoculum containing a) one of 4 single RMS allele variants (A, B, C, D) treated with amoxicillin (AMX 50 mg/kg/dosis, q8h), b) a mixture of all 4 variants with or without AMX treatment or c) different mixtures of 2 RMS allele variants. At selected time points after infection, clinical and inflammatory parameters, bacterial titers and brain damage were determined. Changes in the relative frequency of the occurring RMS allele in the inoculum and in CSF or cerebellum of infected animals were analyzed by capillary electrophoresis. Results We have identified a phase variable RMS locus within L. monocytogenes CC4 and generated stocks that stably expressed each of the possible hsdS genes within that loci. Generation of these allele variants (A, B, C, D) allowed us to determine the methylation pattern associated with each hsdS through SMRT sequencing. In vivo infections with these single allele variants revealed differences in disease severity in that C induced the worst clinical outcome and more pronounced hippocampal apoptosis; D showed the most pronounced weight loss and the highest bacterial titer in the cerebellum. A caused the least severe disease. Conclusion We identified that L. monocytogenes expressing hsdS (A) causes less damage than when other hsdS genes are expressed. While expression of hsdSC and D worsened the outcome in L.monocytogenes meningitis. We also demonstrate a competitive advantage of variants C and B over variant A in this model. Phenotypical switching may therefore represent a mechanism of virulence regulation in CNS infections with L. monocytogenes.